Predicting the aesthetic impact of wind turbines and their influence on landscape value - Rahmani, Shiva; Vito, Pierri; Zuccaro, Luigi; Murgante, Beniamino (TeMA - Journal of Land Use, Mobility and Environment, 2025)
The growing reliance on renewable energy sources (RES) is a direct response to global challenges such as climate change and the limited availability of fossil fuels. Due to their low costs and scale suitability applications, wind turbines and solar panels are among the most widely adopted RES technologies for electricity generation. Their benefits are generally considered to outweigh the disadvantages. However, despite their image as green alternatives these technologies face opposition due to concerns about noise, visual impact, and possible negative effects on ecosystem services. Following the EU Green Deal and its goal of achieving climate neutrality by 2050 the adoption of green energy technologies requiring immediate implementation beyond legislation. The Basilicata region in Italy is among the most affected areas having the highest percentage of wind farms and experiencing notable territorial fragmentation due to their installation. This study aims to assess not only the environmental impacts of wind turbines but also their social and aesthetic effects. Expert-based assessments and spatial analyses will be conducted followed by the Scenic Quality Model within InVEST to evaluate visual impacts. The findings provide valuable insights for policymakers, planners, and researchers involved in sustainable land management and renewable energy planning.